Taxpayer Compliance Behavior: A Qualitative Analysis Of The Impact Of Tax Incentives, Income Levels, And Sanctions - Waruwu, Efendri; Wijaya, Dipa Rizki (STAI Denpasar Bali, 2023)
This qualitative study investigates taxpayer compliance behavior by examining the influence of tax incentives, income levels, and sanctions. Through in-depth interviews and thematic analysis, the research explores the motivations and decision-making processes behind taxpayers' compliance or non-compliance. The findings shed light on the complex interplay between tax policy measures and individual taxpayer behavior, providing valuable insights for policymakers and tax authorities.